Quarter modernization of construction residential "New Praga" in Warsaw - risks and possibilities = Modernizacja kwartału zabudowy mieszkaniowej "Nowej Pragi" w Warszawie, zagrożenia i możliwości - Majewska, Anna; Denis, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The district "New Praga" is located on the right-bank of Warsaw in North Praga which is one of the oldest districts of the city. The citizens of this district, where an analyzed building quarter is located, are people with a lower social status than the rest of Warsaw?s population, who benefit from the social assistance (30%); moreover, there are a large number of crimes and high unemployment among young people in this area.
Keywords: modernizacja zabudowy; kamienica; krajobraz kulturowy; modernization of building; tenement; cultural landscape